New insight into the binding mode of peptides at urotensin‐II receptor by Trp‐constrained analogues of P5U and urantide. (25th March 2013) - Carotenuto, Alfonso; Auriemma, Luigia; Merlino, Francesco; Limatola, Antonio; Campiglia, Pietro; Gomez‐Monterrey, Isabel; di Villa Bianca, Roberta d'Emmanuele; Brancaccio, Diego; Santicioli, Paolo; Meini, Stefania; Maggi, Carlo Alberto; Novellino, Ettore; et al.
Abstract : Urotensin II (U‐II) is a disulfide bridged peptide hormone identified as the ligand of a G‐protein‐coupled receptor. Human U‐II (H‐Glu‐Thr‐Pro‐Asp‐c[Cys‐Phe‐Trp‐Lys‐Tyr‐Cys]‐Val‐OH) has been described as the most potent vasoconstrictor compound identified to date. We have recently identified both a superagonist of human U‐II termed P5U (H‐Asp‐c[Pen‐Phe‐Trp‐Lys‐Tyr‐Cys]‐Val‐OH) and the compound termed urantide (H‐Asp‐c[Pen‐Phe‐d ‐Trp‐Orn‐Tyr‐Cys]‐Val‐OH), which is the most potent UT receptor peptide antagonist described to date. In the present study, we have synthesized four analogues of P5U and urantide in which the Trp 7 residue was replaced by the highly constrainedl ‐Tpi andd ‐Tpi residues. The replacement of the Trp 7 by Tpi led to active analogues. Solution NMR analysis allowed improving the knowledge on conformation–activity relationships previously reported on UT receptor ligands. Copyright © 2013 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Human U‐II (hU‐II) is a disulfide bridged peptide hormone. It is described as the most potent vasoconstrictor compound identified to date. We have recently identified both a superagonist and an antagonist of hU‐II termed P5U and urantide, respectively. We have synthesized four analogues of P5U and urantide in which Trp7 was replaced by the highly constrainedl ‐Tpi ord ‐Tpi residue. This replacement led to active analogues, which allowed improving the knowledge on structure–activity relationships.